The Effectiveness of Online Games on the Learning Mindset of Class 5 Primary Children MIS Nurul Hidayah - Putri, Lisa; Purnama, Tika; Hasibuan, Zohiron (TOFEDU: The Future of Education Journal, 2023)
The variety and convenience offered in these games means they can stay in front of the computer for a long time and their level of use is increasing. This increase in intensive playing and use of online games has given rise to various problems which are known among psychologists as online game addiction. Online games can make players forget time. This happens because the average player is too addicted, and many online game players use the act of playing games as a way to overcome boredom. This research explains the influence of online games on the learning mindset of 5th grade elementary school students, at MIS Nurul Hidayah Jln, Bukit Ngalau, Batu Gadang sub-district, Lubuk Gillian sub-district, Padang city. This research uses survey research methods, where research can find out whether there is an influence online game activities on learning patterns or students. The data collection technique used is to randomly give surveys to people who meet the criteria as respondents.